33.8k views
4 votes
(X-3)^3(x+3)(x+5)^2(x+8)

1 Answer

4 votes

Answer:Simplifying

5(x + 2) = 3(x + 8)

Reorder the terms:

5(2 + x) = 3(x + 8)

(2 * 5 + x * 5) = 3(x + 8)

(10 + 5x) = 3(x + 8)

Reorder the terms:

10 + 5x = 3(8 + x)

10 + 5x = (8 * 3 + x * 3)

10 + 5x = (24 + 3x)

Solving

10 + 5x = 24 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

10 + 5x + -3x = 24 + 3x + -3x

Combine like terms: 5x + -3x = 2x

10 + 2x = 24 + 3x + -3x

Combine like terms: 3x + -3x = 0

10 + 2x = 24 + 0

10 + 2x = 24

Add '-10' to each side of the equation.

10 + -10 + 2x = 24 + -10

Combine like terms: 10 + -10 = 0

0 + 2x = 24 + -10

2x = 24 + -10

Combine like terms: 24 + -10 = 14

2x = 14

Divide each side by '2'.

x = 7

Simplifying

x = 7

Explanation:

User Prototik
by
5.2k points